(12x+8)(4x+14)-(5x+11)(12x+8)=0

Simple and best practice solution for (12x+8)(4x+14)-(5x+11)(12x+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12x+8)(4x+14)-(5x+11)(12x+8)=0 equation:



(12x+8)(4x+14)-(5x+11)(12x+8)=0
We multiply parentheses ..
(+48x^2+168x+32x+112)-(5x+11)(12x+8)=0
We get rid of parentheses
48x^2+168x+32x-(5x+11)(12x+8)+112=0
We multiply parentheses ..
48x^2-(+60x^2+40x+132x+88)+168x+32x+112=0
We add all the numbers together, and all the variables
48x^2-(+60x^2+40x+132x+88)+200x+112=0
We get rid of parentheses
48x^2-60x^2-40x-132x+200x-88+112=0
We add all the numbers together, and all the variables
-12x^2+28x+24=0
a = -12; b = 28; c = +24;
Δ = b2-4ac
Δ = 282-4·(-12)·24
Δ = 1936
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1936}=44$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(28)-44}{2*-12}=\frac{-72}{-24} =+3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(28)+44}{2*-12}=\frac{16}{-24} =-2/3 $

See similar equations:

| (5y+39)+(3y+85)=180 | | 8w-3w=15+10 | | 150m-125m+34,125=35,875+150m | | (8a+11)(2a+14)+(7a+9)(8a+11)=0 | | 7n=(-n)2-18 | | (8a+11)(2a+14)(8a+11)=0 | | 7(+2x)=6(2x-6) | | -8w+3(w+8)=-1 | | 1/2(x-4)=2(x-4) | | -5u+8(u-3)=-18 | | 6v+2(v+6)=-4 | | x5+12=16x5+12=16 | | 5n-8=-23  | | 4.9t^2-3t-1=0 | | 5t^2-3t-1=0 | | 3^2x+4=5^x-5 | | ⅓x+(x-20)+(x-10)+40=360 | | -31=x/5-8 | | (32x)^-4=128 | | –d/5–17=–18 | | Y=-2/5x+5/2 | | w+12/2=2 | | 16+4d=64 | | +30.4+12x=4.9x^2 | | x^2+55x-8750=0 | | (5y+12)(9y+11)-(8y+13)(5y+12)=0 | | -30.4-12x=-4.9x^2 | | -30.4-12x=4.9x^2 | | b–23=2 | | 10(2+y)=30 | | 66/a=11 | | 2n+118=180 |

Equations solver categories